Dampak Sosial dan Ekonomi Dalam Pembangunan Center Point Of Indonesia Kota Makassar - Mawardi, Ahmad Azhar; Nurlinah, Nurlinah; Syamsu, Suhardiman (Kybernology : Journal of Government Studies, 2025)
This study investigates the socio-economic impacts of the Center Point of Indonesia (CPI) development in Makassar City within the paradigm of Sustainable Urban Development. Utilizing a qualitative descriptive design, data were gathered through in-depth interviews with key stakeholders and direct field observations. The findings reveal that the CPI project has stimulated local economic growth through increased investment, tourism expansion, and job creation, particularly in the service and retail sectors. Nonetheless, the project has also triggered significant social and environmental concerns, including disruption of traditional livelihoods, social displacement, and ecological degradation due to coastal reclamation. Anchored in the 5E framework—Environment, Employment, Equity, Engagement, and Energy—this research underscores the need for integrative urban planning that prioritizes inclusive participation, regulatory accountability, and intersectoral coordination. The study contributes to the discourse on sustainable coastal urbanization in developing countries, offering practical insights for policymakers and urban developers